A. V. Prokopenko, A. Kaminina. Interlingual rendering of political terminology. - A. V. Prokopenko; A. Kaminina (Philological Treatises, 2020)
The article deals with the translation of political terms on the basis of the English-speaking political discourse. While investigating journalistic texts, a significant number of abbreviations was found. These abbreviations can be divided into the following: the names of countries; international organizations; defining weapons; international agreements, treaties, pacts. There are difficulties in translation of political abbreviations because some of them do not have the equivalents in the international and political vocabulary. The choice of one or another way of the translation of foreign shortenings in Ukrainian depends on many factors, including the structure of the shortening. The article indicates the peculiarities of the translation of abbreviations used in the political sphere. The results of the research prove that the most frequent ways of translation political abbreviations from English into Ukrainian are: equivalent translation, transliteration, transcription, and descriptive translation.